Dark corners - Rendell, Ruth 1930-2015 (Scribner, 2015)
When Carl sells a box of slimming pills to his close friend Stacey, inadvertently causing her death, he sets in train a sequence of catastrophic events which begin with subterfuge, extend to lies, and culminate in murder. In Rendell's dark and atmospheric tale of psychological suspense, we encounter mistaken identity, kidnap, blackmail, and a cast of characters who are so real that we come to know them better than we know ourselves. Infused with her distinctive blend of wry humour, acute observation and deep humanity, this is Rendell at her most memorable and best